Plasma‐assisted molecular beam epitaxy of strain‐compensated a‐plane InGaN/AlGaN superlattices. Issue 4 (23rd January 2015) - Enck, Ryan W.; Woodward, N.; Gallinat, C.; Metcalfe, G.; Sampath, A. V.; Shen, H.; Wraback, M.
Abstract: Strain‐compensated InGaN/AlGaN structures can enable the growth of thick layers of InGaN epitaxial films far beyond the critical thickness for InGaN grown pseudomorphically to GaN. In this paper, we demonstrate the epitaxial growth of high‐quality strain‐compensated a‐plane In0.12 Ga0.88 N/Al0.19 Ga0.81 N superlattices up to 5 times thicker than the critical thickness on free‐standing a‐plane GaN substrates by plasma‐assisted molecular beam epitaxy (PA‐MBE). The superlattices consist of 50 to 200 periods of 10 nm thick In0.12 Ga0.88 N and 6 nm thick Al0.19 Ga0.81 N layers. The structures are characterized using a double crystal X‐ray diffractometer, asymmetric reciprocal space mapping, and atomic force microscopy. We use X‐ray diffraction to determine the strain, composition, degree of relaxation, and superlattice period of our samples. The structural characteristics of periodic structures containing from 50 to 200 periods are compared to single layer, uncompensated In0.12 Ga0.88 N films. A 100 period structure exhibited only 15% relaxation compared to 69% relaxation for the bulk In0.12 Ga0.88 N film grown with the same total InGaN thickness but without strain‐compensating layers. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)